Study of Biofouling on Fly ash – Bottom ash (FABA) Media Subtract - Selvia Mila; Saptarini Dian (BIO Web of Conferences)
Biofouling is the process of attachment and growth of organisms on the surface of living and non-living objects. Biofouling is one of the biggest issues found on the surface of structures and unwanted organisms. The biofouling process starts from the information of microfouling biofilm (colonization of bacteria and microalgae) and the bacterial biofilm will facilitate the colonization of micro and macroorganisms such as cyanobacteria, fungi, diatoms, barnacles, algae, and protozoa. PLTU is the sector that uses the most coal and has utilized many coastal areas. The combustion results of coal emissions are in the form of fly ash and bottom ash. Fly ash has pozzolan properties containing silica or aluminium reacting with calcium hydroxide, while bottom ash has characteristics resembling sand so that it can be used as a substitute for aggregate and both ashes have the potential as a mixture of concrete substrates and artificial reefs. However, fly ash – bottom ash also contains radioactive pollutants and toxic barium elements that may interfere with the life of biota and the surrounding environment. As in the biota of clams (Mytilus californianus) at the larval level which will be disturbed in the formation of its shell. Marine organisms have a certain influence on the dose value of ash waste received by each biota. It was revealed that there was still accumulation of tube worms and bryozoans in the fly ash – bottom ash concrete substrate, but there was a decrease in diversity, and found eight types of macrofouling in twenty-two concrete feed media, namely tube worms, barnacles, crabs, bryozoans, green algae, tunicates, hydroids, brown algae, sponges, and red algae.